Primary Hydatid Cyst of Skeletal Muscle: A Condition Which is Worth To Be Kept in Mind in The Differential Diagnosis of The Soft Tissue Masses - Kones, Osman; Ilhan, Mehmet; Oner, Osman Zekai; Kalaycı, Mustafa Uygar; Kocatas, Ali; Alıs, Halil (Fırat University, 2012)
Involvement of skeletal muscle in Eccinococcal infection is a relatively rare condition which clinically mimics soft tissue tumors at initial presentation. We present a case report of a 30 years old female patient presented with a painless mass on anterolateral region of her left thigh. Diagnostic work up begun with an MRI examination and it revealed a mass containing multiple cystic vesicles in vastus lateralis muscle which was identical to hydatid disease those seen elsewhere in human body. Surgical excision with Albendazole medication cured the patient. Hydatid disease may present as a painless mass in extremities thus it should be included in differential diagnosis of such masses especially in endemic areas.

Çizgili kasların Ekinokokal infeksiyonu göreceli olarak nadir bir durumdur ve başvuruda klinik olarak yumuşak doku tümörlerini taklit edebilir. Sol uyluğunun anterolateral bölgesinde ağrısız bir kitle ile başvuran 30 yaşında kadın hastayı olgu olarak sunduk. Tetkiklere manyetik rezonans görüntüleme (MRG) ile başlandı. MRG' da vastus lateralis kasının içinde vücüdun diğer yerlerinde görülen kist hidatik ile benzer olan multiple kistik veziküller görüldü. Cerrahi olarak eksize edilerek albendazol tedavisi ile hastada kür sağlandı. Kist hidatik özellikle endemik bölgelerde ekstremitelerde ağrısız kitle olarak belirti verebilir, bu yüzden bu tür kitlelerin ayırıcı tanısında düşünülmelidir.
İskelet Kasının Primer Hidatik Kisti; Yumuşak Doku Kitlelerinin Ayırıcı Tanısında Akla Getirilmesi Gereken Bir Durum